Educational Revolution through Studying the Potential of Artificial Intelligence in Sustainable Development - Loso Judijanto; Asfahani Asfahani; Syatria Adymas Pranajaya; Digvijay Pandey; M. Anwar Aini (Journal of Artificial Intelligence and Development, 2022)
The integration of artificial intelligence (AI) into education has emerged as a transformative force with profound implications for sustainable development. This study explores the potential of AI in revolutionizing educational paradigms to address socio-environmental challenges. The method research through a comprehensive literature review and semi-structured interviews with stakeholders, the research elucidates the role of AI in personalizing learning experiences, enhancing educational outcomes, and fostering critical thinking skills essential for sustainability. The results underscore the importance of ethical considerations and equitable access to AI technologies in ensuring that educational advancements benefit all learners equitably. Building upon prior theoretical frameworks, the study contributes to a holistic understanding of the complex dynamics and implications of leveraging AI in education for sustainable development. Recommendations for future research include exploring innovative pedagogical approaches, assessing long-term impacts, and addressing the digital divide to foster a more inclusive and environmentally sustainable future.